2012
DOI: 10.1111/j.1750-3841.2012.02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Fatty Acid, Essential Oil and Phenolic Contents of Salt‐Treated Sweet Marjoram (Origanum majorana L.) According to Developmental Stage

Abstract: Variation in the composition of Origanum majorana L. essential oil (EO) and fatty acids were studied under salt treatment. Plant material has been harvested at 2 phenological stages: early vegetative stage (EVS) and late vegetative stage (LVS) or prefloral. Our results showed that the application of 75 mM NaCl increased total lipid contents in marjoram shoots and caused great qualitative changes in the fatty acids profiles. NaCl treatment reduced and stimulated the EO yields, respectively, at EVS and LVS and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…These levels of ferulic acid were lower than those of another study on marjoram (Baâtour et al, 2012), which ranged between 6.39 µg/g DW and 37.57 µg/g DW.…”
Section: Multivariate Analysesmentioning
confidence: 44%
See 3 more Smart Citations
“…These levels of ferulic acid were lower than those of another study on marjoram (Baâtour et al, 2012), which ranged between 6.39 µg/g DW and 37.57 µg/g DW.…”
Section: Multivariate Analysesmentioning
confidence: 44%
“…Shan et al (2005) detected protocatechuic acid in sweet basil, dill, star anise and coriander, but not in caraway and nutmeg, while other results in the literature show that protocatechuic acid is not always present in marjoram and turmeric (Papageorgiou et al, 2008;Baâtour et al, 2012). We also found the highest syringic acid levels in marjoram (4.62 µg/g DW), where it has been detected previously (Baâtour et al, 2012). Kivilompolo et al (2007) found less than 50 µg/g DW syringic acid in thyme, with undetectable levels in the other herb extracts analyzed.…”
Section: Multivariate Analysesmentioning
confidence: 74%
See 2 more Smart Citations
“…However, this trend is contradictory to that observed in cucumber [46], Carthamus tinctorius [47,48], Salvia officinalis [30], and Origanum majorana , Zn 2+ contents (µg/g DW) of M. vulgare subjected to different NaCl concentrations (0, 25, 50 and 100 mM) during 5 months. [49]. In the present study, the decrease in TPC could be ascribed to decreased activity of phenylalanine ammonia lyase (PAL: the first enzyme of the phenylpropanoid pathway that catalyzes the elimination of NH 3 from L-phenylalanine to produce trans-cinnamate) probably due to the accumulation of toxic levels of Na + and Cl -.…”
Section: Total Phenolic Contentmentioning
confidence: 78%